Long-run relationship between Malaysian crude palm oil spot and futures market - Salami, Mansurat Ayojimi; Haron, Razali (2014)
This study aims at establishing a long-run relationship of Malaysian CPO futures market using monthly prices from March 1995 to March 2014. Unit-root and Johansen cointegration test are carried out as preliminary test, followed by Vector Error Correction Model (VECM) which is the main econometric approach adopted in this study. The result of this study indicates that Malaysian CPO futures market is efficient and long-run relationship is established between CPO spot and futures prices. Malaysian CPO futures market is found to be a good predictor of the spot market. The result also confirms that the direction of causation from futures market to spot market and this further supports by impulse response functions and variance decomposition. The findings of this study provide essential information to investors of Malaysian crude palm oil market and Malaysian policy maker in commodities markets.